Analisis Kebutuhan Pelatihan Pada PT. Pupuk Kujang Cikampek - Salsabila, Diana Luthfiyyah; Suherman, Enjang; Khalida, Laras Ratu (Jurnal Mirai Management, 2025)
This study aims to identify competency gaps among employees at PT Pupuk Kujang Cikampek and to design relevant training programs based on a Training Needs Analysis (TNA). A descriptive qualitative approach was applied, using interviews, observations, and document analysis as data collection techniques. The findings indicate that the training programs previously implemented have not fully addressed the actual needs in the field. Several issues were identified, including limited understanding of ISO-based risk mitigation, difficulties in troubleshooting machinery, insufficient knowledge of renewable energy technologies, and weak business risk analysis and environmental compliance. Based on the TNA, this study recommends five training programs: machine inspection and maintenance, ISO-based risk analysis, energy audit and industrial efficiency, business and financial risk management, and sustainability strategies and environmental regulation. These training programs are regularly designed to align with the specific needs of each division. The results of this research are expected to support the company in improving the effectiveness of human resource development and training, thereby enhancing operational efficiency and industrial sustainability